PENGARUSUTAMAAN MODERASI BERAGAMA DALAM BUDAYA TRADISI MERTI BUMI SERASI DI KABUPATEN SEMARANG: Sebuah Kajian Makna Simbolik Budaya - Irmawati, Waryunah (Universitas Kiai Abdullah Faqih Gresik, 2025)
Abstract: This study aims to analyze the meaning of symbols contained in the cultural tradition of Merti Bumi Serasi in Semarang Regency which is oriented towards religious moderation, and efforts to mainstream religious moderation. The research approach is descriptive qualitative and phenomenological, while the data analysis method is descriptive, verstehen and interpretation. The theory of analysis to examine the meaning of symbols is the theory of symbol meaning from Roland Barthes, while for the theory of religious moderation used is religious moderation which includes Al Adalah, Tawazun, Tasamuh.. The findings of the research show that starting from the process to the uborambe used, everything has a meaning, namely pitulungan (help) and kawelasan (compassion) harmony, kempel (unity), protection, and gratitude, for the prosperity and blessings given by God Almighty. The values of religious moderation are the value of justice (Al Adalah) in the form of fairness in all aspects as individual creatures of God and social creatures, the value of balance (Tawazun) in the form of maintaining the balance of nature and the value of tolerance (Tasamuh) by involving all elements of religious leaders in the implementation procession. Steps and strategies taken so that the mainstreaming of religious moderation can be realized is the model of cultural evolution and acculturation in the context of nguri-nguri culture. Keyword: Merti Bumi Serasi, Religious Moderation, Meaning of Symbols, Al Adalah, Tawazun, Tasamuh